Endothoracic goiter with atypical progression to the posterior mediastinum: report of two cases (Revista Argentina de Cirugía, 2022)
This paper is focused on two patients who are carriers of endothoracic goiter with atypical growth towards the posterior mediastinum. On the first patient a hemithyroidectomy was performed with a resection of the mediastinum component by a cervicotomy. On the second patient, to the total thyroidectomy, a thoracomy was added to allow for a complete exeresis of the mediastinal tumor
Keywords: endothoracic goiter; posterior mediastinum tumors; thyroidectomy; thoracotomy